(untitled) (World Journal of Vocational Education and Training, 2021)
This study assessed the implementation of entrepreneurship education programme in colleges of education in south-south Nigeria. Three research questions based on curriculum design in terms of objectives and content, methodologies and quality of personnel were raised to guide the study. Also two hypotheses were formulated. Survey research design was used and a sample of 117 lecturers in school of business education from the three federal colleges of education in south-south Nigeria was equally used. The instrument used was a structured questionnaire which consisted of two sections with five point response options. The instrument was validated by two experts in business education and one in measurement and evaluation. Test-retest reliability was used to determine the internal consistency of the instrument and the reliability test coefficient (r) of 0.78 was obtained. Mean and standard deviation were used to analyse data relating to the research questions in order to answer them while t-test was used to test the null hypotheses at 0.05 level of significance. Results of the analysis showed that curriculum design in terms of objective and content, methodologies used in teaching and learning, and retraining of lecturers contributed to effective implementation of entrepreneurship education programme in Federal Colleges of Education in South-South Nigeria. Based on the findings, recommendations were made including that caliber of lecturers; particularly experienced ones involved in the implementation of the programme should be increased.